Small businesses and their challenges during COVID-19 pandemic in developing countries: In the case of Ethiopia - Abriham Ebabu Engidaw (Journal of Innovation and Entrepreneurship, 2022)
Mainly this study was aimed at demonstrating the challenges of small businesses during the corona virus pandemic in developing countries, specifically in Ethiopia. Methodologically, the study deployed secondary data analysis following a descriptive research design. Furthermore, this study was conducted through both qualitative and quantitative research approaches. The secondary data analysis result shows that many small and large businesses are suffering challenges and this unprecedented coronavirus crisis has caused destruction for many businesses in the globe and it is challenging to survive with reduced revenue, jobs lost and life slowing down and weak marketing performance even difficult to keep a calm head and their business alive. To support these businesses, the government should use different mechanisms by cooperating with wealthy peoples and other non-governmental organizations. Besides, small business owners should manage expectations and communicate with staff, suppliers, banks, and customers throughout this coronavirus frightening. Reduce expenses be open to their employees about their finances and keep marketing, use different alternatives to deliver their product, and recover from the crisis.
Keywords: 650; Challenges of small business; COVID-19 pandemic; Small business